The world court of human rights feasibility study - L'ubica Saktorová (DANUBE: Law, Economics and Social Issues Review, 2018)
The idea of the World Court of Human Rights was first envisioned in 1947 along with other institutions designed to create a system capable of the worldwide protection of individual human rights. The focus of the present study is to determine key issues of the prospective establishment of the World Court by an examination of its theoretical position among the United Nations bodies, regional and another inter-governmental human rights organisation. Analysis of the function and mechanisms of the current international human rights protection system would lead to deliberation on the prospective substantial and procedural competences of the World Court, the enforcement mechanism, jurisdiction and related benefits. The objective of the final part is to discuss challenges regarding its political and legal feasibility. Without the visionaries of the past, there would be no substantial system of human rights today. The World Court of Human Rights is a vision for the future.
Keywords: 330; International Human Rights Law; Protection; Judicial System; Feasibility; World Court